Influence of Selected Heparins on Human Neutrophil Functions In Vitro - Labrouche, S; Freyburger, G; Belloc, F; Boisseau, M R (Thrombosis and Haemostasis, 1992)
The effects of four heparin derivatives [unfractionated heparin (UFH) at 5–50 IU/ml, low molecular weight heparin (LMWH) at 2–20 IU/ml, pentasaccharide (Penta) at 5 IU/ml and a synthetic heparinoid (PPS) at 10–6–10–5 M] on various polymorphonuclear (PMN) leukocyte end-functions (aggregation, chemotaxis, phagocytosis and burst) were examined. CR3 expression, actin polymerization and membrane surface charge were also studied to gain more insight on the mechanisms of the action of heparins on PMN. The different heparins were found to have rather different actions. PMN were found to be hyperreactive to PPS. Pentasaccharide hat no effect on PMN functions, while UFH and LMWH had intermediate reactivity, modulating responses in an adenosine-like manner. Interactions of heparins with PMN were attributed to biophysical properties of the molecules rather than to the presence of a specific sequence such as a pentasaccharide.Our results show that certain heparin derivatives, apart their well-known anticoagulant action, modulate polymorphonuclear leukocyte functions that may be involved in vascular injury.